Photocatalytic degradation of 1,4-Benzoquinone in aqueous ZnO dispersions. - Abdollahi, Yadollah; Abdullah, Abdul Halim; Gaya, Umar I.; Ahmadzadeh, Saeid; Zakaria, Azmi; Shameli, Kamyar; Zainal, Zulkarnain; Jahangirian, Hossein; Yusof, Nor Azah (Sociedade Brasileira de Química, 2012)
The present paper reports the UV-assisted degradation of 1,4-benzoquinone in ZnO suspensions. The variables studied include the concentration of 1,4-benzoquinone, photocatalyst, pH and the total organic carbon. The concentration of 1,4-benzoquinone and residue organic carbon were measured using UV-Visible spectrophotometer and TOC analyzer, respectively. The results showed that 1,4-benzoquinone photodegradation was independent of pH. The photoactivity of ZnO was maximum at 1.0 g L-1 concentration and at 100 mg L-1 1,4-benzoquinone levels. Within pH 4-10 more than 80% of 1,4-benzoquinone can be removed. ZnO has demonstrated reusability in the process.